2019
DOI: 10.3389/fphys.2018.01956
|View full text |Cite
|
Sign up to set email alerts
|

Galanin and Adrenomedullin Plasma Responses During Artificial Gravity on a Human Short-Arm Centrifuge

Abstract: Galanin and adrenomedullin plasma responses to head-up tilt and lower body negative pressure have been studied previously. However, to what extent short-arm human centrifugation (SAHC) affects these responses is not known. In this study, we assessed how the application of variable gradients of accelerations (ΔGz) via shifting of the rotation axis during centrifugation affects selected hormonal responses. Specifically, we tested the hypothesis, that cardiovascular modulating hormones such as galanin and adrenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Our study finally enrolled 24 healthy participants (12 females). This population is compatible with previous studies in which cognitive function and hemodynamic parameters were assessed during varying gravitational loading (Stenger et al, 2007;Masatli et al, 2018;Winter et al, 2018;White et al, 2019;Laing et al, 2020) (N = 12-28).…”
Section: Participantssupporting
confidence: 86%
“…Our study finally enrolled 24 healthy participants (12 females). This population is compatible with previous studies in which cognitive function and hemodynamic parameters were assessed during varying gravitational loading (Stenger et al, 2007;Masatli et al, 2018;Winter et al, 2018;White et al, 2019;Laing et al, 2020) (N = 12-28).…”
Section: Participantssupporting
confidence: 86%
“…Once the brain perfusion is reduced to below a critical level, a "vasovagal attack" is triggered, which leads to decreases in heart rate and blood pressure and sudden dilation of the arterial vessels, leading to the loss of consciousness. The following criteria were used for presyncope: heart rate decreases by ≥15 bpm or blood pressure decreases to less than systolic 80 mmHg or by ≥25 mmHg/min; diastolic decreases by ≥15 mmHg/min; and/or nausea, cold-clammy skin or dizziness [24,25].…”
Section: Head-up Tilt (Hut) Testmentioning
confidence: 99%
“…SAHC is routinely used to simulate central hypovolaemia. Our recent work has investigated how applying varying gradients of accelerations (ΔGz) affects galanin and adrenomedullin in subjects which was achieved by shifting the rotation axis during centrifugation. Our findings observed that: (a) baseline galanin values could predict development of presyncope in subjects, and (b) increases in galanin and adrenomedullin levels occur in subjects during elevated levels of central hypovolaemia thus suggesting that galanin and adrenomedullin are important for coping with such stressors.…”
Section: Adrenomedullin and Galanin Responses To Orthostasis In Oldermentioning
confidence: 99%